2009
DOI: 10.3390/medicina45110118
|View full text |Cite
|
Sign up to set email alerts
|

Biomedical physics in continuing medical education: an analysis of learning needs

Abstract: Objective. To examine the learning and practice needs of medical professionals in the field of continuing education of biomedical physics in Lithuania.Material and methods. The study was based on a questionnaire survey of 309 medical professionals throughout Lithuania, 3 focus group discussions, and 18 interviews with medical and physics experts.Results. The study showed that medical professionals lack knowledge of physics: only 15.1% of the respondents admitted that they had enough knowledge in biomedical phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…A sound understanding of basic sciences is key for the successful completion of medical education. It has been shown that a fundamental knowledge of basic sciences is a major determinant of diagnostic success [ 1 , 2 ]. Therefore, it is indispensable to improve the quality of teaching and to meet the needs of medical students in terms of usefulness, especially in basic sciences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A sound understanding of basic sciences is key for the successful completion of medical education. It has been shown that a fundamental knowledge of basic sciences is a major determinant of diagnostic success [ 1 , 2 ]. Therefore, it is indispensable to improve the quality of teaching and to meet the needs of medical students in terms of usefulness, especially in basic sciences.…”
Section: Discussionmentioning
confidence: 99%
“…A sound knowledge and understanding of basic sciences are a prerequisite for a successful completion of medical education. Fundamental knowledge in basic sciences serves as a major determinant of diagnostic success, because numerous modern devices and methods used for diagnostics and treatments are based on these [1,2]. Nevertheless, there is a significant variance in students' basic science knowledge at the beginning of medical education [3].…”
Section: Introductionmentioning
confidence: 99%
“…This is surprising as whilst in the case of pharmaceuticals often little input is required by the healthcare professional (above calculation of dosage and assessment of side effects or contra-indications), a device will only function effectively and safely if properly utilized and cared for by the professional. Yet, learning about devices within healthcare organizations is often an unsatisfactory process -the reasons ranging from trial-and-error learning to training sessions from vendor 'application specialists' which are too short or simply insufficient (Rotomskis, Karenauskaite, & Balzekiene, 2009;Vano et al, 2007). The situation is becoming more critical as devices increase in sophistication, capability and number of user options; in fact, devices are developing at such a rate that education is simply not keeping pace.…”
Section: Medical Device Education For Healthcare Professionals -A Sit...mentioning
confidence: 99%